Fabrication Method for the High-Accuracy Optical Fiber Delay Line with Specified Length - Ruoxian Liu; Shiyuan Zhao; Yiying Gu; Runze Yu; Pengcheng Deng; Mingshan Zhao (Photonics, 2023)
We propose a novel scheme for fabricating high-accuracy optical fiber delay lines (OFDLs). The fabrication system integrates a self-designed optical fiber cutting device and a high-accuracy fiber length measurement module based on optical frequency domain reflectometry. The optical fiber cutting device can cleave optical fibers to a specific length with the help of the motorized stage. The accuracy of fiber-cutting was determined by the positional accuracy of the motorized stage, which can reach several microns or even lower. This integrated design significantly reduces the errors and uncertainties introduced by fiber-cutting. To test, a set of OFDLs of a certain length was fabricated by this system. The deviation from the desired fiber length was kept below 50 μm, thus proving high fabrication accuracy and repeatability.